The Role of Employee Retention in Improving Sustainable Employee Performance at Proklamasi Ent Hospital BSD - Feni Endah Trisnawati; Muhammad Fachruddin Arrozi Adhikara; Ratna Indrawati (Inovasi Kesehatan Global, 2025)
Sustainable employee performance is one of the important factors in achieving organizational competitive advantage. This study is based on the trend of declining performance in 2023 at the Proklamasi BSD ENT Hospital. The purpose of this study is to analyze the effect of human resource development and ambidexterous leadership on sustainable employee performance with job retention as an intervening variable. This type of research includes quantitative causality design. The population used is permanent employees who have worked for more than 3 years. The sampling technique is saturated sampling totaling 101 people. The data collection technique uses a questionnaire, the analysis method uses Structural Equation Modeling with the help of SPSS AMOS 26. The results of the analysis prove that simultaneously human resource development, ambidexterous leadership has a positive effect on sustainable employee performance and job retention as an intervening variable. The importance of additional training and support, improving communication regarding educational opportunities, evaluating how tasks are carried out and ensuring employees have an appropriate workload.